Persepsi Mahasiswa Semester 7 Terhadap Pelayanan Akademik di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado - Soba, Siane; Pangemanan, Damajanty; Natalia, Adriani (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Organization within a university to be able to provide high-quality services, supported by an accountable evaluation system. Assessment of the student perception, which is one aspect of the quality of educational services, is important for the development of the education system. The results of student satisfaction levels can be used to direct a better education system. The aim of this study is to determine student perceptions of academic services for 7th-semester students in the Nursing Science Study Program, Faculty of Medicine, University of Sam Ratulangi Manado. The method used is descriptive-analytical with a cross-sectional study approach. The sample amounted to 71 respondents obtained by using the Total Sampling technique. The results of the research on student perceptions of academic services based on the five dimensions of service are good, services that are considered good based on student perceptions, namely on the reliability service dimension in the employee's statement greeting students in a friendly manner, on the responsiveness service dimension in the lecturer's statement very responsive to student affairs, on the warranty service dimension on statement every time completing administrative tasks clear and accurate communication, as well as a friendly and sympathetic attitude are always shown by study program staff, on the empathetic service dimension in the statement the lecturer staff is very helpful and understands students who experience difficulties in subjects and academics, and on the service dimension tangible in statements each teaching staff is equipped with digital tools such as computers and social media to facilitate services to students. The conclusion in this study is that the perception of students in academic services for 7th-semester students at the Sam ratulangi University Nursing Science Study Program is good. Expected for institutions to continue to provide the best quality service, taking into account the five dimensions of good service, which are: reliability, responsiveness, assurance, empathy, and tangibles. Keywords: Academic Service; Perception; Student